2022
DOI: 10.3390/foods11131962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cocoa Beverage and Dark Chocolate Consumption on Blood Pressure in Those with Normal and Elevated Blood Pressure: A Systematic Review and Meta-Analysis

Abstract: Cocoa is a major dietary source of polyphenols, including flavanols, which have been associated with reduced blood pressure (BP). While earlier systematic reviews and meta-analyses have shown significant effects of cocoa consumption on systolic BP, limitations include small sample sizes and study heterogeneity. Questions regarding food matrix and dose of polyphenols, flavanols, or epicatechins remain. This systematic review and meta-analysis aimed to investigate the effects of ≥2 weeks of cocoa consumption as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 62 publications
1
17
0
1
Order By: Relevance
“…The amount of (-)epicatechin as a reliable marker of total flavanol content in commercially available chocolate products shows large variation. To achieve comparable amounts to the flavanols used in the present supplement, approximately 240 -900 g of dark chocolate would be required [38][39][40] . Cocoa flavanols have been shown…”
Section: Acute and Long-term Functional Impairment After Vascular Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of (-)epicatechin as a reliable marker of total flavanol content in commercially available chocolate products shows large variation. To achieve comparable amounts to the flavanols used in the present supplement, approximately 240 -900 g of dark chocolate would be required [38][39][40] . Cocoa flavanols have been shown…”
Section: Acute and Long-term Functional Impairment After Vascular Injurymentioning
confidence: 99%
“…To achieve comparable amounts to the flavanols used in the present supplement, approximately 240-900 g of dark chocolate would be required. [38][39][40] Cocoa flavanols have been shown to improve CVD risk biomarkers, including FMD and blood pressure, in individuals of different CVD risk categories ranging from healthy to established CVD. 16 Potential mechanisms include modulation of the inflammatory response through NF-κB, TNFα, and IL-1β cascades.…”
Section: Acute and Long-term Functional Impairment After Vascular Injurymentioning
confidence: 99%
“…The types of antioxidants based on their solubility can be found in Table (3). A fatsoluble antioxidant acts primarily on the membranes of cells, whereas a watersoluble antioxidant acts both within and outside the cell.…”
Section: Small -Molecule Antioxidantsmentioning
confidence: 99%
“…The effects of cocoa consumption were examined in one meta-analysis in which researchers compared the effects of cocoa consumption on patients with normal and high blood pressure. It has been shown that dark chocolate, which contains a high concentration of cocoa, is more effective than cocoa beverages at lowering blood pressure (Amoah et al, 2022).…”
Section: Small -Molecule Antioxidantsmentioning
confidence: 99%
“…მუქმა შოკოლადმა შეამცირა სისტოლური არტერიული წნევა უფრო მეტად, ვიდრე კაკაოს სასმელმა. ფლავანოლების ან ეპიკატექინის დღიური დოზის მატება კაკაოს და შოკოლადის პროდუქტებში, აძლიერებდა წნევაზე ზემოქმედების ეფექტს [4]. შოკოლადის და კაკაოს ნიმუშების კვლევის დროს აღინიშნება დადებითი კორელაცია პოლიფენოლების რაოდენობასა და ანტიოქსიდანტურ აქტივობას შორის [5] მასალა და მეთოდები.…”
unclassified